Pengaruh Kepercayaan, Harga Dan Layanan Terhadap Keputusan Kontrak Kerja Pada PT. Jaya Alumindo Perkasa Medan - Butar-Butar, Mangasi; Gunawan, Siegfried; Stevic, Stevic; Aston, Mario; Ferdinand, Juan Rio; Gultom, Robinhot (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Jaya Alumindo Perkasa is a company that operates in the contracting sector and is located in Medan, where currently the company is experiencing problems with consumer purchases where every year, the number of consumers who make purchases continues to decline, so this impacts the company's growth and development. Researchers took the population in this study as 187 customers who made purchases from the company. The sample determination technique that will be used is to use the Slovin formula with a tolerance level of 5% where with the calculations carried out, 127 samples were obtained. The research results show that partially or simultaneously Trust, Pricing and Service have a significant influence on Purchasing Decisions at PT. Jaya Alumindo Perkasa Medan. The ability of the Trust (X1), Pricing (X2), and Service (X3) variables to explain their influence on Purchasing Decisions (Y) is 62.2%. Meanwhile, the remaining 37.8% is the influence of other independent variables not examined in this research.